2022
DOI: 10.1021/acs.jafc.2c06691
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Aryloxy-, Arylthio-, and Arylamino-Containing Acethydrazides as Fungicidal Agents

Abstract: The development of new green fungicides is an effective way to solve the resistance of agricultural pathogens and plays an important role in promoting high-quality and sustainable development of modern agriculture. In this project, a series of aryloxy-, arylthio-, and arylamino-containing acethydrazide derivatives were designed, synthesized, and characterized by 1 H nuclear magnetic resonance (NMR), 13 C NMR, and high-resolution mass spectrometry (HRMS). The fungicidal bioassays indicated that some compounds s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 32 publications
2
31
1
Order By: Relevance
“…The investigation of wheat seedling growth treated with the hydrazide compounds was achieved according to our previous work . First, 150 full-grain wheat seeds were prepared, sterilized with 75% alcohol, washed with distilled water, and placed uniformly in five Petri dishes with two filter papers in advance to culture at 25 °C for 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…The investigation of wheat seedling growth treated with the hydrazide compounds was achieved according to our previous work . First, 150 full-grain wheat seeds were prepared, sterilized with 75% alcohol, washed with distilled water, and placed uniformly in five Petri dishes with two filter papers in advance to culture at 25 °C for 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…Hua’s group , synthesized a series of aryloxy-, arylthio-, and arylamino-containing acethydrazide derivatives 4 (Figure ). The fungicidal bioassays indicated that some compounds showed excellent and broad-spectrum inhibitory activity, of which compounds 4a (X = O, R 1 = 2-F, 4-F) and 4b (X = NH, R 1 = 2-F, 4-F) exhibited inhibitory effects against P. grisea superior to other compounds, with EC 50 values of 0.59 and 0.86 μg/mL.…”
Section: Structures and Activity Of Hydrazide Derivativesmentioning
confidence: 99%
“…Additionally, compounds 85 , 88 , and 89 were also constructed with laccase inhibitors coumarin hydrazone and PMDD-5Y as lead structures and thus proved to be laccase inhibitors as well. However, authors Chen and Fang pointed out, respectively, that the monohydrazide compounds 2f and 4c significantly affected the normal function of plasma membranes, which was different from the fungicidal mechanisms mentioned above. As we know, the plasma membrane is composed of phospholipid bilayers, including glycerophospholipids, sphingolipids, and sterols. Subsequently, with the help of transcriptomics and metabolomics, author Fang found that the fungicidal mechanism of hydrazide compound 4c was involved in some specific differential genes and differential metabolites in the plasma membrane-associated linoleic acid metabolism, arachidonic acid metabolism, α-linoleic acid metabolism, and sphingolipid metabolism pathways.…”
Section: Summary and Future Prospectsmentioning
confidence: 99%
See 2 more Smart Citations